2012
DOI: 10.1097/brs.0b013e3182443855
|View full text |Cite
|
Sign up to set email alerts
|

Association of Modic Changes, Schmorlʼs Nodes, Spondylolytic Defects, High-Intensity Zone Lesions, Disc Herniations, and Radial Tears With Low Back Symptom Severity Among Young Finnish Adults

Abstract: Herniations were most likely in the subjects with recent onset or persistent (3-yr period) low back symptoms, although they were also detected in subjects with no symptoms. The clinical relevance of herniations on MRI remains to be evaluated in the context of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 68 publications
1
49
1
2
Order By: Relevance
“…However, annular fissures, high-intensity zone lesions, Modic changes, and spondylotic defects were not associated with low back pain severity. 11 They also demonstrated that disk degeneration was found in one-third of asymptomatic 21-year-olds. 11 A systematic review of 12 studies found no consistent association between low back pain and MR imaging findings of Modic changes, disk degeneration, and disk herniation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, annular fissures, high-intensity zone lesions, Modic changes, and spondylotic defects were not associated with low back pain severity. 11 They also demonstrated that disk degeneration was found in one-third of asymptomatic 21-year-olds. 11 A systematic review of 12 studies found no consistent association between low back pain and MR imaging findings of Modic changes, disk degeneration, and disk herniation.…”
Section: Discussionmentioning
confidence: 95%
“…11 They also demonstrated that disk degeneration was found in one-third of asymptomatic 21-year-olds. 11 A systematic review of 12 studies found no consistent association between low back pain and MR imaging findings of Modic changes, disk degeneration, and disk herniation. 12 In a large case control study, vertebral endplate changes were not associated with chronic low back pain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[21][22][23][24] On the contrary, prevalence of disc extrusions ranged from 5% to 10% in symptomatic populations. [21][22][23][24] One surprising finding from our study was that disc bulge had a strong association with low back pain. Because of the high prevalence in the asymptomatic population, disc bulges are often considered incidental findings and not associated with low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, recent medical imaging data from healthy patients have led to SNs being regarded as a common phenomenon in healthy adults, with their cause and prevalence being a continued subject of debate. [5][6][7] The aims of this study were to use kinematic magnetic resonance imaging (k-MRI) to investigate the positional distribution of SNs along the lumbar spine in adults without persistent lumbar spine related disorders, their relationship to lumbar disk degeneration, and their association with changes in lumbar spine motion. These results expanded on previous studies of SN distribution in the asymptomatic lumbar spine by demonstrating a relationship between SNs, posture, and range of motion.…”
mentioning
confidence: 99%